Model Design, Simulation and Control of a Robotic Arm using PIC 16F877A Microcontroller - Buji, A. B.; Mshelia, Y. P.; Ibrahim, A. G.; Sarki, M. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper focuses on model design, simulation and control of a five degree of freedom (DoF) robotic arm using servo motors. The robotic arm is controlled by a PIC 16F877A microcontroller and its main function is to generate pulse width modulation (PWM) signals which are applied to the servo motors for achieving the desired rotation angle. A PWM signal could have different effects on various servo motors depending on their specifications. Thus, it is important to apply the exact PWM signals to achieve the rotation angle desired. The main advantage of controlling the servo motors with PWM signals is that they can be programmed to have an initial position and to rotate with an exact degree with respect to the requirements. A general formula is derived for finding the pulse width required to achieve the desired rotation in each servo motor. The main advantage of this formula is that it can be used for any servo motor with different specification. Simulation results presented showed that for PWM signal (P) a difference of 0.45s to 1.45µs and angle rotation difference of 0.04º to 0.11º were obtained. The results obtained from the derived equation is found to have 98% accuracy compared to the simulation results.